Mechanistic and functional studies on biliverdin IXa reductase from the cyanobacterium synechocystis sp.PCC6803 - Hayes, Jerrard Michael (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2009)
The enzymes of heme metabolism and phycobilin biosynthesis in the cyanobacterium Synechocystis sp. PCC6803, along with their reducing partners, ferredoxin and ferredoxin reductase were produced through recombinant DNA techniques and displayed the appropriate molecular weights on SDS-PAGE. Antibodies were raised against the recombinant heme oxygenase 1 (HO1), biliverdin IXa reductase (sBVR-A) and phycocyanobilin ferredoxin oxidoreductase (PcyA).
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin.